Study of antiarrhythmic activity of some 1,8-disubstituted of theobromine - Parla, Charishma (Запорізький державний медичний університет, 2022)
The aim of the study: to investigate antiarrhythmic and cardioprotective activity of some newly synthesized derivatives of some new 1,8-disubstituted of theobromine [compounds 1-5].
Keywords: тези доповідей